2021
DOI: 10.1002/iid3.416
|View full text |Cite
|
Sign up to set email alerts
|

Current research status of HLA in immune‐related diseases

Abstract: Human leukocyte antigen (HLA), also known as human major histocompatibility complex (MHC), is encoded by the HLA gene complex, and is currently known to have the highest gene density and the most polymorphisms among human chromosomal areas. HLA is divided into class I antigens, class II antigens, and class III antigens according to distribution and function. Classical HLA class I antigens include HLA‐A, HLA‐B, and HLA‐C; HLA class II antigens include HLA‐DP, HLA‐DQ, and HLA‐DR; nonclassical HLA class I and II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 93 publications
2
40
0
3
Order By: Relevance
“…Third, TLR4 initiated signaling is involved in the regulation of osteoblast differentiation and function [ 32 , 34 ]. Several such immunoregulatory mediators are also included in an osteoblast-specific protein–protein interaction network (see Figure 2 ; CD14, TANK, TRAF6) together with immunoregulatory HLA molecules [ 36 ]. Thus, our osteoblast-specific protein interaction network seems to be involved in a crosstalk between osteoblasts and regulators of inflammation/immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Third, TLR4 initiated signaling is involved in the regulation of osteoblast differentiation and function [ 32 , 34 ]. Several such immunoregulatory mediators are also included in an osteoblast-specific protein–protein interaction network (see Figure 2 ; CD14, TANK, TRAF6) together with immunoregulatory HLA molecules [ 36 ]. Thus, our osteoblast-specific protein interaction network seems to be involved in a crosstalk between osteoblasts and regulators of inflammation/immunity.…”
Section: Discussionmentioning
confidence: 99%
“…2.2.5. Human Leukocyte Antigen-Major Histocompatibility Complex, DR, B1 (HLA-DRB1) HLA-DR is a major histocompatibility complex (MHC) class II cell receptor encoded on chromosome 6 region 6p21.31 [81]. It serves as a ligand for the T-cell receptor (TCR) and is involved in multiple autoimmune conditions.…”
Section: Lymphotoxin α (Lt-α) or Transforming Growth Factor β (Tgf-β) And Interferon γ (Ifn-γ)mentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) of immune-related genes contribute to the onset of disorders and immune reactivity 7 . Previous studies by Petersdorf et al revealed that the rs2242656 of BAG6, rs986522 of COL11A2, rs2244546 of HCP5, rs2523957 of MICD, rs429916 of HLA-DOA, rs2071479 of HLA-DOB, rs107822 of RING1, and rs209130 of TRIM27 are related to the risk of relapse, survival rate, or graft-versus-host disease (GVHD) in patients receiving bone marrow stem cell transplantation 8 .…”
Section: Introductionmentioning
confidence: 99%